Reactive oxygen species may influence on the crossroads of stemness, senescence, and carcinogenesis in a cell via the roles of APRO family proteins - Yuka Ikeda; Kurumi Taniguchi; Nozomi Nagase; Ai Tsuji; Yasuko Kitagishi; Satoru Matsuda (Open Exploration Publishing Inc., 2021)
Excessive reactive oxygen species (ROS) may cause oxidative stress which is involved in aging and in the pathogenesis of various human diseases. Whereas unregulated levels of the ROS may be harmful, regulated basal level of ROS is even necessary to support cellular functions as a second messenger for homeostasis under physiological conditions. Therefore, redox medicine could develop as a new therapeutic concept for human health-benefits. Here, we introduce the involvement of ROS on the crossroads of stemness, senescence, and carcinogenesis in a stem cell and cancer cell biology. Amazingly, the anti-proliferative (APRO) family anti-proliferative proteins characterized by immediate early growth responsive genes may also be involved in the crossroads machinery. The biological functions of APRO proteins (APROs) seem to be quite intricate, however, which might be a key modulator of microRNAs (miRNAs). Given the crucial roles of ROS and APROs for pathophysiological functions, upcoming novel therapeutics should include vigilant modulation of the redox state. Next generation of medicine including regenerative medicine and/or cancer therapy will likely comprise strategies for altering the redox environment with the APROs via the modulation of miRNAs as well as with the regulation of ROS of cells in a sustainable manner.